Eggstra-ordinary: 3-D adventure - Tracey West; Craig McCracken (New York, Scholastic, 2002)
"Princess Morbucks has just devised her most sinister scheme ever. The spoiled Powerpuff wanna-be has hidden monster eggs all over Townville. When those eggs hatch, the city will be swarming angry. HUNGRY baby monsters! Can the Girls save the city---and the day? Well, that's up to YOU! Use the 3-D glasees inside this book to help Blossom, Bubbles, and Buttercup find those eggs ..."